Insights into the application of soccer-specific actions in established and new game forms of youth soccer - Lex, H.; Simon, M.; Schwab, S. (German Journal of Exercise and Sport Research, 2022)
Soccer is constantly changing regarding the demands of the new generation. At its best, young players develop outstanding technical and tactical skills as well as a wealth of competition experience. In addition to targeted training, maintaining motivation is one of the biggest challenges facing youth coaches. One possible way is to build their confidence while having fun. As a new game form, 3 vs. 3 unites the main events of the soccer game, challenges young players in a versatile manner, and promotes joy. In the present study, 23 games played in the new and 16 games played in the established competitive styles (7 vs. 7 and 6 vs. 6) were compared and analyzed regarding the variables passing, dribbling, shooting, and scoring. MANOVA revealed a significant effect for the factor game form: F(4,33) = 8.974, p < 0.001, n2 = 0.521. Additionally, post-hoc comparisons (using Sidak correction) indicated a significantly higher number for the occurrence of each game event in the new game form. This finding suggests an increased involvement. Child-friendly small-sided games (SSG; like the new game form) will help to promote children in the best way and inspire them to play soccer for a long time.